National Intelligence University's role in interagency research : recommendations from the intelligence community - Johnston, Judith A.; Lander, Natasha; McInnis, Brian (Research report (Rand Corporation), 2013)
The Center for Strategic Intelligence Research (CSIR) of the National Intelligence University (NIU) is responsible for supporting faculty and student research efforts and coordinating NIU research activities with the Intelligence Community (IC). A challenge to these coordination efforts lies in the fact that research being conducted regularly in the IC exists, for the most part, in small pockets scattered throughout a number of different IC agencies. To better identify collaborative research opportunities, topics, and processes, CSIR asked RAND to conduct a study that would capture information about these research entities, their responsibilities, and their willingness to support interagency research with NIU. The study team conducted semistructured interviews with a purposive sample of representatives of research entities in the IC. The interviews discussed interagency research and collaboration with NIU. We found that the majority of these research entities are small (less than ten full-time staff), face the competing responsibilities of short-term analytic responses and longer-term analysis and research, and are interested in research plans aligned with national priorities. The research entities are willing to support NIU, but expect NIU to take the lead in facilitating research collaboration.